2016
DOI: 10.5152/etd.2016.0090
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of E-cadherin, Endothelin-1, and CD68 in Preeclamptic Placentas

Abstract: Objective: Preeclampsia (PE) is a complex pregnancy-specific disorder characterized by the onset of hypertension and proteinuria in the second trimester of pregnancy. The pathogenesis of PE still remains unknown. Revealing the specific proteins involved in placental functions is important for a better understanding of the pathogenesis of PE. In this study, we aimed to investigate the expression levels of E-cadherin, endothelin-1, and CD68 in both preeclamptic and normal placentas. Materials and Methods:In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Contrary to the result of present study, some studies have reported that placental ET-1 expression was significantly higher in preeclamptic placentae than in normal placentae, 12 13 whereas other studies have reported that ET-1 mRNA expression was significantly lower in preeclamptic placentae than in normal placentae. 14 In these studies, placental ET-1 mRNA expression was determined by northern-blot analysis, 12 real-time polymerase chain reaction (RT-PCR) 14 and western blot.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the result of present study, some studies have reported that placental ET-1 expression was significantly higher in preeclamptic placentae than in normal placentae, 12 13 whereas other studies have reported that ET-1 mRNA expression was significantly lower in preeclamptic placentae than in normal placentae. 14 In these studies, placental ET-1 mRNA expression was determined by northern-blot analysis, 12 real-time polymerase chain reaction (RT-PCR) 14 and western blot.…”
Section: Discussioncontrasting
confidence: 99%
“…11 However, there are still controversial findings concerning the level of placental ET-1 in normal pregnant women and those with PE. Studies have found that the levels of tissue endothelin in placental tissues were higher, 12 13 lower, 14 or not significantly different 8 15 16 in preeclamptic pregnant women compared with normal pregnant women.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, E-cadherin is a cell-cell adhesion protein that plays a crucial role in controlling the invasive phenotype of placenta accrete extravillous trophoblasts [31]. A previous study confirmed the high expression of E-cadherin in the preeclamptic placenta [32]. N-cadherin is also a key EMT marker involved in trophoblast invasion [33].…”
Section: Discussionmentioning
confidence: 91%
“…Migration of CD8 + memory cells largely depends on the binding of P-and E-selectins, the expression of which increases in the presence of IL-15 [66]. CD8 + T lymphocytes are characterized by expression of the CXCR6 receptor, which, through interaction with the chemokine CXCL16 secreted by trophoblast, attracts T lymphocytes to the decidua [52]. CD103 expression can be associated with the migration of CD8 + Treg into the inflam mation zone [56,84].…”
Section: Differentiation Of Cd8 + T Lymphocytesmentioning
confidence: 99%
“…Currently, there is no consensus on the persistence of the population of cytotoxic lymphocytes in the decidua during pregnancy. Some authors claim that during the pregnancy, the amount of CD8 + T lymphocytes in the decidua of women does not change [145] and is 45-75% of the T lymphocytes of the decidua (T lymphocytes constitute 10-20% of decidual leukocytes) [34,52,93]. Other authors point out a different content of cytotoxic lymphocytes in the decidua, depending on the period of pregnancy.…”
Section: Differentiation Of Cd8 + T Lymphocytesmentioning
confidence: 99%